Pendidikan Kesehatan Media Short Education Movie (SEM) Terhadap Pengetahuan Dan Sikap Remaja Tentang Seks Bebas - Zulfa Suhailah; Tiyas Kusumaningrum; Aria Aulia Nastiti (Pediomaternal Nursing Journal, 2019)
Introduction: Sexual health problems in adolescents are increasing every year. Sexual aspects of adolescence such as free sex, unwanted pregnancy, abortions, high rape, sexual harassment, circulation of pornographic contents are today. SEM is a short film that contains a learning process with a duration of less than 50 minutes. Health education with media SEM (Short Educaation Movie) the aims of this research was to analyze the effect of health education on adolescent knowledge and attitudes about free sex.Methods: Design of this research used the Quasy Experiment. The population in this study were all students of Darma Siswa Vocational High School amounted to 182 students. The sample size in this study was 124 samples consisted of students of Darma Siswa Vocational High School class X. The independent variable in this research was health education with the media Short Education Movie (SEM). The dependent variable in this study is adolescent knowledge and attitudes about free sex. The inclusion criteria are students of class X, aged 15-16 years. Exclusion criteria are students who do not enter school and students who follow the practice outside of school, students who are taking part in the national exam preparation. Data were collected using a questionnaire, then analyzed data with the Wilcoxon Sign Rank Test and Mann Whitney U Test.Results: The results of this study found that knowledge and attitudes of students of Darma Siswa Vocational High School increased after being given health education with the media Short Education Movie (SEM) with a significance value of p=0,000.Conclusion: Short Education Movie (SEM) is a health education media that can improve adolescent knowledge and attitudes about free sex and provide appropriate information through health education.